The Art of Scientific Research Design - the first of the Five Stages : Justification of Research Objectives - Govil, Kailash C.; Verma, Anjali (Indian Forester, 1997)
The entire process of research design is a multi-faceted process of providing verifiable, precise, effective, objective and ethical research. The conceptualization of the research design"is, therefore, very crucial to the research. The research design can be divided into two components i.e. technical and administrative. The technical component consists of the justification of the research objectives, review of literature, conceptual framework, observation and analysis, and inference drawing. The administrative component includes estimate of money. Time, personnel and management aspects. Once the concepts of research design are clear and unambiguous, skilled researchers/scientists can Gse the whole arsenal of research techniques - observation, content analysis of documents, testing, search of cxistingrecords, laboratory experiments, measurements of physical evidence and analytical methods to answer hislher research question in a robust and efficient manner.